PENGARUH PENGANGGARAN DANA DESA TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT KECAMATAN PALABUHANRATU KABUPATEN SUKABUMI - Yusuf Umar; Wati Karmila (STISIP Widyapuri Mandiri, 2022)
This study uses a quantitative approach. The population of this study were all employees of Palabuhanratu Subdistrict, Palabuhanratu Subdistrict employees and 9 village apparatuses throughout Palabuhanratu Subdistrict totaling 156 people and the number of samples was taken 70% of the total population so that a sample of 109 people was obtained. The calculation results show that the Village Fund Budgeting variable in Palabuhanratu District is included in the good category with an average score of 3.45 or 69.00% of the ideal value, while the economic empowerment of the community in Palabuhanratu District is included in the sufficient category with an average score of 3.39 or 67.80% of the ideal value. The results of statistical analysis obtained the price of rXY = 0.527 which is included in the criteria is quite strong. With a significance value (2-tailed) 0.000 <0.05 or tcount = 6.414 > ttable = 1.982, so it can be concluded that there is an effect of the Village Fund budget on community economic empowerment in Palabuhanratu District. The coefficient of determination (KD) is 0.2777, meaning that the contribution of the village fund budget variable (X) to the community economic empowerment variable (Y) in Palabuhanratu District, Sukabumi Regency is 27.77%, and the remaining 72.23% is determined by other factors. While the linear regression equation model obtained is Y = 21.176 + 0.507X